Broken promises in crowdfunded projects: reasons and mitigating governance mechanisms. (28th July 2022) - Shtepa, Sophia; Osiyevskyy, Oleksiy
Reward-based crowdfunding is a popular method of obtaining financing for new ventures, allowing to attract funding for projects from numerous individual backers, who pledge small amounts of money in return for future products/services, discounts, acknowledgement, or branded merchandise. Yet, more than half of all crowdfunded projects deliver rewards to backers late (i.e., after the promised date), and around 5% do not deliver at all. Relying on the premises of bounded reliability and bounded rationality of project creators, we pose the following research questions: 1) What are the reasons for failed commitments (i.e., delayed or cancelled delivery) in crowdfunded projects? 2) Which governance mechanisms prevent these failed commitments? We address these questions using a qualitative investigation of reward-based crowdfunded projects, comparing cases of successful and failed implementation.